A Nonsense Mutation in MSX1 Causes Witkop Syndrome - Jumlongras, Dolrudee (The American Society of Human Genetics, 2001)
Witkop syndrome, also known as tooth and nail syndrome (TNS), is a rare autosomal dominant disorder. Affected individuals have nail dysplasia and several congenitally missing teeth. To identify the gene responsible for TNS, we used candidate-gene linkage analysis in a three-generation family affected by the disorder. We found linkage between TNS and polymorphic markers surrounding the MSX1 locus. Direct sequencing and restriction-enzyme analysis revealed that a heterozygous stop mutation in the homeodomain of MSX1 cosegregated with the phenotype. In addition, histological analysis of Msx1-knockout mice, combined with a finding of Msx1 expression in mesenchyme of developing nail beds, revealed that not only was tooth development disrupted in these mice, but nail development was affected as well. Nail plates in Msx1-null mice were defective and were thinner than those of their wild-type littermates. The resemblance between the tooth and nail phenotype in the human family and that of Msx1-knockout mice strongly supports the conclusions that a nonsense mutation in MSX1 causes TNS and that Msx1 is critical for both tooth and nail development.